Effect of steam explosion on waste copier paper alone and in a mixed lignocellulosic substrate on saccharification and fermentation. (July 2015) - Elliston, Adam; Wilson, David R.; Wellner, Nikolaus; Collins, Samuel R.A.; Roberts, Ian N.; Waldron, Keith W.
Highlights: Steam explosion of copier paper reduces xylose and produces inhibitors. Steam explosion at SF 3.6 and 3.9 increased initial rates of saccharification. Steam explosion at moderate severities may reduce processing times. Co-steam explosion of waste paper and wheat straw reduces inhibitor production. Abstract: This study evaluated steam (SE) explosion on the saccharification and simultaneous saccharification and fermentation (SSF) of waste copier paper. SE resulted in a colouration, a reduction in fibre thickness and increased water absorption. Changes in chemical composition were evident at severities greater than 4.24 resulting in a loss of xylose and the production of breakdown products known to inhibit fermentation (particularly formic acid and acetic acid). SE did not improve final yields of glucose or ethanol, and at severities 4.53 and 4.83 reduced yields probably due to the effect of breakdown products and fermentation inhibitors. However, at moderate severities of 3.6 and 3.9 there was an increase in initial rates of hydrolysis which may provide a basis for reducing processing times. Co-steam explosion of waste copier paper and wheat straw attenuated the production of breakdown products, and may also provide a basis for improving SSF of lignocellulose.